Jenna Broomhead: capstone - Broomhead, Jenna, artist (Colorado State University. Libraries, 2023)
The artist's statement: In my work, I delve into the interplay between patterns and representational images, aiming to create visually striking and lively scenes through the use of strong colors and repetition. I juxtapose bold colors with softer, more subdued hues to achieve a balanced and harmonious composition. My ultimate goal is to elicit powerful emotional responses from the viewer by employing simple shapes to express complex ideas and emotions and limiting my color palette to highlight the narrative of my work. I often incorporate patterns or abstract concepts to communicate a range of ideas and messages, working closely with clients to refine their vision and create thoughtful and evocative pieces.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design